Training routine and motivation among crossfit® participants in Brazil and Portugal during the covid-19 pandemic: an observational study - Arthur Marques Zecchin-Oliveira; Rafael A. M. Domiciano; Victor Barbosa Ribeiro; Enrico Fuini Pugina (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2021)
In late 2019, a new coronavirus was identified in Wuhan, Hubei province, China. Considering the transmission characteristics, public health actions have been indicated such as social distance, guidance on staying at home, quarantine and traffic restriction. There are some strategies to enhance immune system that can fight virus, decreasing its efficacy. Moderate intensity physical exercise demonstrated before to prevent many infectious diseases. In this paper, is detailed the characteristics of motivation and training status of CrossFitÂ® practitioners during corona virus quarantine, in Brazil and Portugal. Its hypothesized that CrossFitÂ® participants are doing high-intensity training (HIT) and they are highly motivated during quarantine, independent of the country. 263 CrossFit® participants volunteered to participate in this study (231 from Brazil and 32 from Portugal). Questions about motivation level was related with other questions (how many partners training, together, intensity, training frequency per week, etc). The aspects of "how many participants are training together", "sessions per week", "spreadsheet training utilization", "intensity of the workouts" and "motivation" demonstrated significance. There are a significant number of CrossFit® participants in Brazil and Portugal who are training HIT in their workouts, and it can suppress the immune system. Motivation and training routine demonstrated impairment. Coaches and trainers in general must control training intensity and keep the participants highly motivated, through strategies that avoid long period of HIT and high-volume training in quarantine.